Hubungan Teori Belajar dengan Pembelajaran Pendidikan Agama Islam - Marlina, Yeni (Lembaga Yasin AlSys, 2024)
The aim of this research is to understand the importance of applying learning theories to Islamic Religious Education learning. The method used by the author is a literature review which takes sources from books, journals, articles, websites, etc. & attempts to explain the application of learning theory so that it can produce changes in behavior towards students & also its relationship with Islamic Religious Education learning. Based on the research results, it was found that the application of learning theory in PAI learning uses reinforcement, motivation, stimulus and practice. Meanwhile, changes in student behavior in a positive direction are motivated in learning, interactive, strengthening memory, and tolerance.